Diagnostic accuracy of simultaneous evaluation of coronary arteries and myocardial perfusion with single stress cardiac computed tomography acquisition compared to invasive coronary angiography plus invasive fractional flow reserve. (15th December 2018) - Pontone, Gianluca; Baggiano, Andrea; Andreini, Daniele; Guaricci, Andrea I.; Guglielmo, Marco; Muscogiuri, Giuseppe; Fusini, Laura; Soldi, Margherita; Del Torto, Alberico; Mushtaq, Saima; Conte, Edoardo; Calligaris, Giuseppe; et al.
Abstract: Background: Coronary computed tomography angiography (cCTA) has limited diagnostic accuracy in patients with intermediate to high pre-test likelihood of coronary artery disease (CAD) that may have large amounts of coronary calcium. Stress computed tomography myocardial perfusion (CTP) has emerged as a valuable strategy, combining anatomical and functional assessment of CAD. Purpose of the study is to evaluate the diagnostic accuracy of combining coronary artery imaging and myocardial perfusion in a single stress dataset versus invasive coronary angiography (ICA) and invasive fractional flow reserve (FFR) as reference standard. Methods: One-hundred-thirty consecutive symptomatic patients (age: 65 ± 9 years; men: 70%) scheduled for clinically indicated ICA plus invasive FFR were prospectively enrolled. cCTA + CTP were simultaneously evaluated in a single stress-dataset by blinded readers and compared to ICA and invasive FFR findings. Results: CTP was successfully performed in all patients. The most common artifacts observed in the stress dataset for coronary artery imaging were blooming effect and motion effect related. Overall evaluability of coronary arteries by using cCTA stress dataset was 93%. In a vessel and patient-based model, stress cCTA + stress CTP showed sensitivity, specificity, negative predictive value, positive predictive value and diagnostic accuracy of 93%, 94%, 97%, 85%, 94%, and 98%, 86%, 98%, 85%, 92%, respectively. The overall effective dose (ED) of stress protocol acquisition alone was 2.5 ± 1.1 mSv. Conclusions: Simultaneous evaluation of coronary arteries and myocardial perfusion with single stress acquisition is feasible and it has diagnostic accuracy and low ED to identify functionally significant stenosis in patients with intermediate to high risk for CAD. Highlights: Single stress acquisition for simultaneous evaluation of coronary arteries and myocardial perfusion has high accuracy It is possible to obtain anatomical and functional data with a single acquisition with less than 3 mSv. Only a minority of patients may need a second rest-scan deriving a benefit in terms of radiation exposure and contrast load.